From classroom to wedding aisle: The effect of a nationwide change in the compulsory schooling law on age at first marriage in the UK - Nattavudh Powdthavee; Kampon Adireksombat (Institute for the Study of Labor (IZA), 2010)
Does more schooling causes a delay in marriage? Using a nationwide change in the compulsory schooling law in the UK as a source of exogenous variation in education, this paper estimates the causal effect of schooling on age at first marriage. The 1947 reform, which uniquely affected about a half of the relevant population, led to a jump in the average age at first marriage for both genders, with the effect being much more statistically robust for men than women. The regression discontinuity and IV estimates imply that completing an extra year of schooling increases the average age at first marriage by approximately 3 years for men and almost 2 years for women. Given the compelling effect of the 1947 reform, it is likely that our reduced form estimates come close to mirroring the ATE for the general population.
Keywords: I2; J12; N34; 330; Compulsory schooling; age at first marriage; regression discontinuity; human capital; family formation; Schulrecht; Wirkungsanalyse; Ehe; Altersgruppe; Schätzung; Großbritannien